Utilization of Gamification Technology and its Implication on Learning Al-Qur'an Hadith at Madrasah Aliyah Negeri 1 Probolinggo City - Muchtar, Wardatul Maulidina; Achmadin, Balya Ziaulhaq; Syarifah, Hasnia Imroatis; Fattah, Abdul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This research explores the application of gamification technology in teaching Al-Qur'an Hadith at Islamic Senior High School 1 Probolinggo City. The aim of this study is to examine the impact of gamification on students' learning motivation and participation. Using a qualitative research approach, data were collected through field observations, in-depth interviews, and document analysis. The findings indicate that integrating gamification technology into Al-Qur'an Hadith learning can enhance students' motivation and participation. While gamification is often applied in science and technical subjects, this research focuses on religious education, particularly Al-Qur'an Hadith, which is often perceived as less engaging by students, offering novelty in applying gamification technology in a different context. The results show that gamification can create an interactive and enjoyable learning environment, even in religious subjects like Al-Qur'an Hadith, significantly increasing students' motivation and participation in the learning process. Gamification engages students with game elements such as points, levels, and challenges, making learning more appealing. However, this study also highlights the importance of teacher preparation and adequate infrastructure to ensure the effective application of gamification technology. For a more engaging learning experience, it is crucial that teachers are trained to integrate this technology into their lesson plans. In conclusion, while gamification offers significant pedagogical benefits, it should complement, not replace, the essential role of teachers. A balance between technology and human interaction is vital for the success of a gamified learning environment.